A concise review of the bioanalytical methods for the quantitation of sitagliptin, an important dipeptidyl peptidase‐4 (DPP4) inhibitor, utilized for the characterization of the drug. (14th March 2016) - Suresh, P. S.; Srinivas, Nuggehally R.; Mullangi, Ramesh
Abstract: Inhibition of dipeptidyl peptidase‐4 (DPP4) is an emerging therapeutic approach for treating type 2 diabetes and has revolutionized the concept of diabetes management. Sitagliptin is the first approved orally active, potent, selective and nonpeptidomimetic DPP4 inhibitor. Incidence of hypoglycemia and weight gain is negligible with sitagliptin treatment. It is used as monotherapy or in combination with other anti‐diabetic drugs to treat type 2 diabetes. There are numerous bioanalytical methods published for the analysis of sitagliptin in preclinical and clinical samples. This review focuses on the various HPLC and LC‐MS/MS methods that have been used to analyze sitagliptin in various biological matrices. A small section is devoted to the bioanalysis of other DPP4 inhibitors such as vildagliptin, saxagliptin and linagliptin. This review provides key information in a concise manner regarding sample processing options, chromatographic/detection conditions and validation parameters of the chosen methods for sitagliptin and other DPP4 inhibitors. Copyright © 2016 John Wiley & Sons, Ltd.